1978
DOI: 10.1136/jnnp.41.10.894
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between regional cerebral blood flow and brain atrophy in dementia. Combined study with 133Xenon inhalation and computerised tomography.

Abstract: S U M MARY Measurement of the regional cerebral blood flow (rCBF) by the 133xenon inhalation method and computerised tomography were performed in 25 patients with presenile and senile deni6ntia. Reduction of rCBF and various degrees of ventricular enlargement and cortical sulcal widening were demonstrated in the majority of demented subjects. However, there was no correlation between rCBF values and the severity of ventricular dilatation or cortical atrophy. These findings suggest that loss of brain substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These findings are consistent with our own results. Yamaguchi et al [13] reported that CBF was closely correlated with brain atrophy in normal elderly sub jects; however, Melamed et al [14] reported that there was no correlation between CBF values and severity of ventricular dilatation or cortical atrophy in patients with presenile or senile dementia. There have been, how ever, few reports on the relation between CBF and brain atrophy in MID.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with our own results. Yamaguchi et al [13] reported that CBF was closely correlated with brain atrophy in normal elderly sub jects; however, Melamed et al [14] reported that there was no correlation between CBF values and severity of ventricular dilatation or cortical atrophy in patients with presenile or senile dementia. There have been, how ever, few reports on the relation between CBF and brain atrophy in MID.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic striatal atrophy accompanied by ventricular dilatation and cortical sulcal widening have been demonstrated by pneumoencephalography [7] and computed tomography (CT) [2,34, 451. Although extensive studies have been performed in presenile and senile dementia using measurements of cerebral blood flow (CBF) [21,31, 331, oxygen utilization [16,17, 291, and glucose utilization (CMRgI,) [5, 13, 191, these methods have rarely been applied to H D .The necessity of measuring brain function, blood flow, metabolism, and structure locally rather than globally is now recognized. Previously, we found that in both stroke [27] and epilepsy [25], altered lo-cal glucose utilization (LCMR,,,), determined by positron emission computed tomography of 18Ffluorodeoxyglucose (FDG) [36, 381, is a more sensitive indicator of altered local cerebral function than is the accompanying structural abnormality determined by CT.…”
mentioning
confidence: 99%
“…Characteristic striatal atrophy accompanied by ventricular dilatation and cortical sulcal widening have been demonstrated by pneumoencephalography [7] and computed tomography (CT) [2,34, 451. Although extensive studies have been performed in presenile and senile dementia using measurements of cerebral blood flow (CBF) [21,31, 331, oxygen utilization [16,17, 291, and glucose utilization (CMRgI,) [5, 13, 191, these methods have rarely been applied to H D .…”
mentioning
confidence: 99%
“…As well, a decrease in cerebral blood flow (CBF) may be associated with brain atrophy. However, previous studies have failed to find a significant relationship between CBF and brain atrophy in patients with dementia [7,8,9]. In patients with cerebral artery occlusive disease, atrophy of the corpus callosum was reported to progress in concert with the deterioration of cerebral cortical oxygen metabolism in small population studies [10, 11].…”
Section: Introductionmentioning
confidence: 99%